Pengaruh Influencer Marketing, Citra Merek, dan Electronic Word Of Mouth Terhadap Keputusan Pembelian pada Marketplace Shopee - Jackson, Jackson; Inda Sukati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of influencer marketing, brand image, and e-WOM on purchasing decisions on the Shopee marketplace. A quantitative descriptive approach was used, involving 204 Shopee consumers who had previously purchased specific products. They were selected using purposive sampling based on Jacob Cohen's calculation guidelines to ensure the sample accurately represented the population. Data were collected through a questionnaire, which was then analyzed using validity and reliability tests, classical assumption evaluation, multiple linear regression, and hypothesis testing using t-tests and F-tests. The regression analysis showed that influencer marketing had a 34.8% influence on purchasing decisions, brand image contributed 32.7%, and e-WOM had an influence of 20.0%. Furthermore, the coefficient of determination (R²) showed that these three variables together explained 86.9% of the variation in consumer purchasing decisions. The t- and F-tests confirmed that each variable had a significant and positive influence, both partially and simultaneously, on purchasing decisions on the Shopee marketplace.